Correction of a mucogingival defect using an implant-retained postoperative stent in a severely resorbed mandible: Case report - De Melo, Luiz Gustavo Nascimento; Ciporkin, Fredenco; Neto, José Sérgio Maia; De Almeida, Ana Lúcia Pompéia Fraga; Lopes, José Fernando Scarelli; Figueiredo, Caio Márcio; Nagata, Maria José Hitomi [UNESP] (My University, 2008)
This case report describes a technique that uses a palatal mucosal graft and an acrylic resin postoperative stent in an attempt to increase the layer of keratinized tissue around osseointegrated implants in an atrophic mandible. During second- stage surgery, a split-thickness labial flap is reflected and apically repositioned by being sutured onto the periosteum and connective tissue. A palatal mucosal graft is then sutured onto the recipient site. The stent is worn for at least 4 weeks following surgery. This procedure helps to eliminate mobility of the mucosa in the area, deepen the vestibule, and prevent muscle reinsertion.